Pemahaman Ilmu Tajwid Melalui Metode Sorogan Pada Mata Pelajaran Al-Qur’an - Rohmad; Afifah, Siti Nur (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2022)
This research aims to find out how the sorogan method is used to understand the science of tajwids. Using qualitative approaches and case studies, research that takes the research objects of students of class V MI Darussalamah Sumbersari, Kepung, Kediri results in the conclusion that the sorogan method is an effective method in the subjects of the Qur'an in class V MI Darussalamah. With this method the achievement of learning outcomes is very maximal and satisfactory. The advantage of the sorogan method is that the teacher can know exactly the quality that has been achieved by students. While the shortcomings of the sorogan method are inefficient because it only faces a few students (no more than 5 people), so if facing many students this method is less precise.